Additions to the genus Neostasina Rheims & Alayón (Araneae: Sparassidae: Sparianthinae) - Rheims, Cristina A.; Alayón, Giraldo (European Journal of Taxonomy, 2022)
The genus Neostasina Rheims & Alayón is revisited. New material is examined, resulting in the description of seven new species: N. aceitillar sp. nov. (♀), N. bani sp. nov. (♂♀), N. demaco sp. nov. (♀) from Dominican Republic, N. juanita sp. nov. (♀), N. paraiso sp. nov. (♂♀), N. toronegro sp. nov. (♀) from Puerto Rico, and N. maisi sp. nov. (♂♀) from Cuba. New distribution records are given for N. amalie, N. cachote, N. guanaboa, N. iberia, N. saetosa, N. siempreverde and N. turquino. In addition, an updated identification key and updated distribution maps for all species of the genus are provided.